KARAKTERISASI TAPIOKA DARI LIMA VARIETAS UBI KAYU (Manihot utilisima Crantz) ASAL LAMPUNG - Elvira Syamsir; Purwiyatno Hariyadi; Dedi Fardiaz; Feri Kusnandar (Faculty of Agricultural Technology, University of Jember, 2011)
The physicochemical and functional properties of starches (tapioca) from five varieties Manihot utilisima Crantz (Thailand, Kasetsar, Pucuk Biru, Faroka and Adira-4) from Lampung were evaluated. All tapioca samples showed a typical A-type diffraction pattern, indicating that variety had no effect on it. However, the starch crystallinity was affected. Some parameters of physicochemical and functional of tapioca from five varieties varied significantly (p < 0,05). Analysis of correlation showed that amylose, fat, ash as well as crystalinity and swelling power affected some of pasting and gel texture parameters. Digestion of gelatinized starch was also affected by root varieties. Keywords: physicochemical properties, pasting, texture, crystalinity